Which strength manifestation is more related to regional swimmers` performance and in-water forces? Maximal neuromuscular capacities versus maximal mechanical maintenance capacity - Miras-Moreno, S.; López-Belmonte, Ó.; García-Ramos, A.; Arellano, R.; Ruiz-Navarro, J. J. (International Journal of Sports Physiology and Performance, 2024)
Purpose To explore the association of the load-velocity (L-V) relationship variables and ability to maintain maximal mechanical performance during the prone bench-pull exercise with sprint swimming performance and in-water forces.